2022
DOI: 10.3390/life12040508
|View full text |Cite
|
Sign up to set email alerts
|

New Signatures of Bio-Molecular Complexity in the Hypervelocity Impact Ejecta of Icy Moon Analogues

Abstract: Impact delivery of prebiotic compounds to the early Earth from an impacting comet is considered to be one of the possible ways by which prebiotic molecules arrived on the Earth. Given the ubiquity of impact features observed on all planetary bodies, bolide impacts may be a common source of organics on other planetary bodies both in our own and other solar systems. Biomolecules such as amino acids have been detected on comets and are known to be synthesized due to impact-induced shock processing. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…The shocked ice samples were then analyzed showing the presence of a series of amino acids, including glycine, (D)-alanine, (L)-alanine, and (L)-isovaline [ 16 ]. Similar experiments have more recently been performed by Singh et al [ 120 ] at the same facility [ 121 ] by using more complex bullets composed of icy amino acids which, after being shot at a speed of ∼5 km· , have been transformed into complex biological structures such as peptides and membranelike structures.…”
Section: Results and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The shocked ice samples were then analyzed showing the presence of a series of amino acids, including glycine, (D)-alanine, (L)-alanine, and (L)-isovaline [ 16 ]. Similar experiments have more recently been performed by Singh et al [ 120 ] at the same facility [ 121 ] by using more complex bullets composed of icy amino acids which, after being shot at a speed of ∼5 km· , have been transformed into complex biological structures such as peptides and membranelike structures.…”
Section: Results and Discussionsupporting
confidence: 55%
“…The fact that glycine and other prebiotically relevant species were detected in non-negligible amounts in some comets, such as Halley, Hyakutake, Tempel-1, Giacobini–Zinner, Hartley 2 and Hale–Bopp, 81P/Wild 2 [ 105 , 106 , 107 , 108 , 109 , 110 , 111 ], indirectly suggested the possibility to observe and reproduce a relatively complex chemistry when high-energy impacts take place. In fact, many interesting experimental and computational results emerge from disparate investigations of the catalytic effects produced by violent mechanical stresses acting on simple inorganic systems [ 7 , 16 , 18 , 36 , 39 , 42 , 104 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 120 ]. As an example, Martins et al [ 16 ] created several icy bullets composed of simple compounds ubiquitous in cometary ices such as ammonium hydroxide (NH 4 OH), carbon dioxide (CO 2 ), and methanol (CH 3 OH), which were impacted on a series of rocky surfaces—mimicking planetary surfaces—by using a light gas gun available at an important facility located at the University of Kent [ 121 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…Analyzing the impact of shock waves on the surface characteristics of the crystalline and non‐crystalline samples at dynamic shock wave exposed conditions is one of the interesting research areas by which the nature of the aftermath effect of the crystallographic structural phase features experienced by the samples could be identified specifically. [ 54 ] Recently, Surendra Singh and his research group have demonstrated the shock wave processing on amino acid materials and a few bio‐molecular complex materials and they have found significantly modified surface morphologies at shocked conditions. [ 54 ] Furthermore, technologically important inorganic material of ammonium dihydrogen phosphate poly‐crystalline material has been subjected to shock waves and performed the particle surface analysis by which it has been found that, during the shocked conditions, the prismatic face undergoes a significant defect formation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 54 ] Recently, Surendra Singh and his research group have demonstrated the shock wave processing on amino acid materials and a few bio‐molecular complex materials and they have found significantly modified surface morphologies at shocked conditions. [ 54 ] Furthermore, technologically important inorganic material of ammonium dihydrogen phosphate poly‐crystalline material has been subjected to shock waves and performed the particle surface analysis by which it has been found that, during the shocked conditions, the prismatic face undergoes a significant defect formation. [ 47 ] In addition to that, as per the previous article, during the shocked conditions, single‐crystalline NaNO 3 crystals experience significant changes on the surface of the crystals.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known that impacts can produce more complex molecules from simpler precursors (e.g., Bar-Nun et al, 1970;Blank et al, 2001;Peterson et al, 1997;Sugahara & Mimura, 2015;Takeuchi et al, 2020). Of particular interest here is that, it has previously been shown that impacts involving ices can drive chemistry (e.g., Bowden et al, 2009;Nna-Mvondo et al, 2008;Singh et al, 2022). Indeed, it has also been shown that amino acids can be produced in impacts onto ices (Martins et al, 2013).…”
Section: Particles Larger Than a Micrometermentioning
confidence: 96%